Relationship between interdialytic weight gain and nutritional status of chronic kidney disease patients on hemodialysis (Research, Society and Development, 2022)
Introduction: Interdialytic weight gain (IDWG) is an important marker of adherence to dietary restrictions in individuals on hemodialysis (HD). Objective: To evaluate the association between nutritional indicators and IDWG in HD patients in the Metropolitan Region of Greater Vitória/ES. Method: This is a cross-sectional study developed with 1024 patients on HD. Results: The GPID was raised to 30.5% (n=311) of the individuals, and those with excess weight and high waist circumference presented, respectively, 46% (OR 0.540, 95%CI 0.394-0.741) and 44% (OR 0.540, 95%CI 0.394-0.741) less chance of inadequate GPID. However, those who presented muscle depletion according to arm muscle circumference (OR 1.421, 95%CI 1.009-2.002) and by corrected arm muscle area (OR 1.435, 95%CI 1.052-1.958) had approximately 1.4 times more chances of high weight gain between dialysis sessions. Conclusion: Individuals with muscle depletion are more likely to have high GPID, while having greater body mass decreased the chances of this inadequate weight gain.